Modelling and Simulation on Penetration into Stone Concrete - He Huang; Duo Zhang; Lirong Cheng (Advances in Materials Science and Engineering)
Penetration into stone concrete is an important research area of concrete penetration, and related experiments and simulation tests have been carried out. However, complete theories have not been formed yet. This paper develops a differential facet resistance model for penetration into stone concrete target. Firstly, the plastic damage model is used to analyze the penetration of concrete target, and the reliability of the numerical model is verified by comparing with the classical experimental results. Besides, the numerical model of stone concrete is established based on 3D Voronoi diagram according to the random characteristics of the shape and spatial distribution of stones in concrete. Then, simulation tests are carried out with the validated numerical model, a differential facet resistance model suitable for the penetration of stone concrete target is then proposed referring to the resistance formula of Forrestal and Rosenberg. At last, a method for fast calculation of penetration into stone concrete is introduced.